Functional Gastrointestinal Disorders in a Primary Care Pediatric Clinic. (23rd January 2015) - Stein, Ronen; Chelimsky, Thomas; Li, Hong; Chelimsky, Gisela
Functional gastrointestinal disorders (FGIDs) are a common problem in pediatric patients and can affect quality of life. However, the extent of these disorders may vary in different subpopulations of children. This study investigated the prevalence of FGIDs in an inner-city primary care practice. Healthy patients between the ages of 9 and 17 were administered a validated questionnaire that assessed for FGIDs and other somatic complaints. Eleven of 145 patients (7.5%) met criteria for FGIDs based on Rome III Diagnostic Criteria. Raynaud-like symptoms tended to occur more often in patients meeting criteria for FGIDs, although this association was not statistically significant ( P = .07). The lower prevalence of FGIDs in this population compared with earlier studies may suggest a link between socioeconomic status and the prevalence of FGIDs. Larger population-based studies consisting of a heterogeneous cohort from a variety of socioeconomic backgrounds are necessary to further elucidate the true connection between FGIDs and socioeconomic status.